The Influence Of Customer Relationship Management And Customer Satisfaction On Customer Loyalty - Kotteeswaran, S.; Murugan, R. (Journal of Neonatal Surgery, 2025)
Customer Relationship Management (CRM) is a widely implemented model for managing a company’s interactions with customers and sales prospects. It involves using technology to organize, automate, and synchronize business processes, primarily those related to sales activities, but also marketing, customer service, and technical support. The overall objectives of CRM are to find, attract, and acquire new customers; nurture and retain existing ones; win back former customers; and reduce the costs of marketing and customer service. CRM represents a company-wide business strategy that includes customer-facing departments as well as other internal departments. The primary aim of this study is to analyze customer relationship management practices in the context of products and services. The research is conducted by collecting feedback from customers and comparing those results with expected outcomes. By studying and comparing customer perceptions of products and services, businesses can build more effective relationships with their customers. Maintaining strong customer relationships is crucial, as it helps organizations establish a competitive position in the market.